Building the Agile enterprise : with capabilities, collaborations and values - Cummins, Fred (Cambridge, MA : Morgan Kaufmann, 2016)
Annotation Building the Agile Enterprise with Capabilities, Collaborations and Values, Second Edition covers advances that make technology more powerful and pervasive while, at the same time, improving alignment of technology with business. Using numerous examples, illustrations, and case studies, Fred Cummins, an industry expert, author and former fellow with EDS and Hewlett Packard, updates his first edition incorporating the following industry developments:The ubiquitous use of the Internet along with intelligent, mobile devices, which have enabled everyone and everything to be connected anytime, anywhereThe emergence of a business architecture discipline that has driven improvements in business design and transformation practicesThe development of CMMN (Case Management Model and Notation) that will provide automation to support the collaboration of knowledge workers and managersThe development of VDML (Value Delivery Modeling Language) that supports modeling of business design from a management perspectiveThe importance of big data management and analysis as a new source of insight into evolution of the business and the ecosystemHow the architecture of the agile enterprise and business modeling change enterprise governance, management and innovationBuilding the Agile Enterprise with Capabilities, Collaborations and Values, Second Edition is a must have reference for business leaders, CTOs; business architects, information systems architects and business process modeling professionals who wish to close the gap between strategic planning and business operations as well as the gap between business and IT and enhance the creation and delivery of business value.Explains how business design abstraction based on collaborations, capabilities and values provides a management view of how the business works, the aspects to be improved or changed, and the means to quickly reconfigure to address new business challenges and opportunitiesDiscusses how technology must be exploited for efficiency, effectiveness, innovation and agilityProvides practicable and use-case based insights from advisory work with Fortune 100 and 500 companies across multiple verticalsPresents the features of CMMN (Case Management Model and Notation) and explains how it enables automation to support knowledge workers, managers and enterprise agilityDescribes application of the Value Delivery Modeling Language (VDML) to link strategic business transformation to operational design"
Includes bibliographical references and index.
Keywords: Information resources management; Management information systems; Agile software development; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Agile software development; Information resources management; Management information systems; Electronic books